Depth of invasion in superficial oral tongue carcinoma quantified using intraoral ultrasonography. (16th October 2018) - Iida, Yoshiyuki; Kamijo, Tomoyuki; Kusafuka, Kimihide; Omae, Katsuhiro; Nishiya, Yukio; Hamaguchi, Noriko; Morita, Kotaro; Onitsuka, Tetsuro
Abstract : Objective: Depth of invasion (DOI) in oral carcinoma has been integrated into the primary tumor categories in the current tumor‐node‐metastasis staging (8th edition). However, there is no standard modality to determine DOI preoperatively. The aims of the present study were to evaluate the accuracy of a preoperative measurement of DOI using ultrasonography (US) for superficial oral tongue carcinomas, and to correlate the values obtained with histologically determined DOI measurements. Methods: We retrospectively analyzed the records of 56 patients with oral tongue carcinoma who underwent intraoral US preoperatively, followed by curative surgery at the Shizuoka Cancer Center Hospital in Japan. For the measurement of DOI with US, our unique technique (water balloon method) was evaluated. Results: The histologically measured tumor size (maximum diameter) showed a distribution of 7.0 to 40.0 mm (mean, 18.6 mm). The correlation between the US‐obtained and histologically obtained DOIs was significant (r = 0.867; P < 0.001). In tumors characterized histologically as superficial (DOI ≤ 5 mm), a significant correlation was observed between US‐obtained and histologically obtained DOIs (r = 0.870, P < 0.001). For the entire cohort, the sensitivity and specificity of US assessment of DOI of ≤ 5 mm or > 5 mm were 92.3% and 70.6%, respectively. Conclusion: Intraoral US provides sufficient accuracy for the measurement of tumor DOI in oral tongue carcinoma and is complementary in assessing superficial lesions. Level of Evidence: 4. Laryngoscope, 128:2778–2782, 2018